1994
DOI: 10.1254/jjp.65.99
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Study of Chicken Calcitonin Gene-Related Peptide (CGRP) on Vasorelaxation in Rat Mesenteric Resistance Vessels.

Abstract: ABSTRACT-Structure-activity relationship of the chicken calcitonin gene-related peptide (cCGRP) was investigated and compared with human-a-CGRP (hCGRP) and rat CGRP (rCGRP) in the perfused mesenteric vascular beds of rats. In precontracted mesenteric vascular beds, cCGRP, hCGRP and rCGRP produced a concentration-dependent vasodilation. The vasodilator activities of cCGRP and rCGRP were equipotent and more potent than that of hCGRP. (Ala2,')cCGRP and (Des-l-Ala)-a-deamino cCGRP were 100 and 10-fold less potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…However, the CGRP antagonist, CGRP 8–37 , did not reduce the effects of either capsaicin or CGRP. At the concentrations used in the present study, CGRP 8–37 has previously been reported in rat mesenteric arteries to reduce the vasodilator actions of both exogenously applied and neurally released CGRP ( Claing et al , 1992 ; Nuki et al , 1994 ). Furthermore, the samples of CGRP 8–37 used in the present study did increase the force of neurally evoked contractions of rat mesenteric arteries mounted in a wire myograph (results not shown), indicating that they were able to reduce the basal level of inhibition due to CGRP released from the primary afferent innervation (see Kawasaki et al , 1990 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, the CGRP antagonist, CGRP 8–37 , did not reduce the effects of either capsaicin or CGRP. At the concentrations used in the present study, CGRP 8–37 has previously been reported in rat mesenteric arteries to reduce the vasodilator actions of both exogenously applied and neurally released CGRP ( Claing et al , 1992 ; Nuki et al , 1994 ). Furthermore, the samples of CGRP 8–37 used in the present study did increase the force of neurally evoked contractions of rat mesenteric arteries mounted in a wire myograph (results not shown), indicating that they were able to reduce the basal level of inhibition due to CGRP released from the primary afferent innervation (see Kawasaki et al , 1990 ).…”
Section: Discussionsupporting
confidence: 53%
“…CGRP receptors have been divided into two classes on the basis of their sensitivity to the blocking actions of CGRP 8–37 ; CGRP 1 (p A 2 >7) and CGRP 2 (p A 2 <7) ( Poyner et al , 2002 ). In rat mesenteric artery, the p A 2 for rat CGRP 8–37 against the vasodilator actions of rat CGRP has been reported to be 7.4 ( Nuki et al , 1994 ). Therefore, the vasodilator actions of CGRP are classified as being mediated through CGRP 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that for hα CGRP 8–37 , both vasodilator and vasoconstrictor effects have been reported. For instance, a vasodilator component was noted in rabbit skin, in vivo (Hughes & Brain, 1991) and cat cerebral vasculature (Wahl et al ., 1994), while vasoconstriction was observed in rat perfused mesenteric artery (Han et al ., 1990; Nuki et al ., 1994b), perfused kidney (Chin et al ., 1994) and the rat vasculature, in vivo (Gardiner et al ., 1990). Therefore, the present findings illustrate that not only hα CGRP 8–37 but also its analogues have limitations as antagonists, underlining the need for more selective compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that human-aCGRP(8 ± 37) has competitive antagonistic activity in pig coronary arteries with a pK B value of 6.7 (Gray et al, 1991). In rat mesenteric small artery, the pK B value falls within the range 7.2 to 7.6 Lei et al, 1994;Nuki et al, 1994). In rat thoracic aorta, human-aCGRP(8 ± 37) seems to be a non-competitive antagonist of human-aCGRP (Gray et al, 1991) adding to the complexity of CGRP-receptor characterization.…”
Section: Discussionmentioning
confidence: 99%